1999
DOI: 10.1583/1074-6218(1999)006<0042:sittor>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Stents in the Treatment of Renal Artery Stenosis: Long-term Follow-up

Abstract: Renal artery stenting is safe, effective, and may be an alternative to surgery, particularly in ostial lesions. Our experience shows reduction in the restenosis rate compared to conventional angioplasty. All ostial stenoses should be stented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(25 citation statements)
references
References 26 publications
3
12
0
2
Order By: Relevance
“…The average restenosis rate, evaluated between 6 and 12 months after the procedure, was 16%. A second meta-analysis, comparing renal stent (733,735). In those series, the 5-year primary patency rates of renal stents were 79% and 84.5%, and the secondary patency rates were 92.4% and 98%.…”
Section: Catheter-based Interventionsmentioning
confidence: 99%
“…The average restenosis rate, evaluated between 6 and 12 months after the procedure, was 16%. A second meta-analysis, comparing renal stent (733,735). In those series, the 5-year primary patency rates of renal stents were 79% and 84.5%, and the secondary patency rates were 92.4% and 98%.…”
Section: Catheter-based Interventionsmentioning
confidence: 99%
“…72 These excellent results were confirmed by Henry and associates, 73 who reported a cumulative primary patency rate of 78.8% and a secondary patency rate of 97.8% at 6 years (72 to 78 months) of follow-up.…”
Section: Restenosismentioning
confidence: 68%
“…37,71 More recent reports suggest that with optimal deployment techniques, restenosis rates of less than 15% can be achieved. 59,62,72,73 Renal artery restenosis after stent placement is related to both acute gain and late loss, similar to restenosis after coronary artery intervention. We performed quantitative angiography on a series of 100 consecutive patients and found that patients with patent renal arteries at 8-month follow-up had significantly larger postprocedure minimal lumen diameter (4.3Ϯ0.7 mm versus 4.9Ϯ0.9 mm; Pϭ0.025) and had significantly less late loss (1.3Ϯ0.9 mm versus 3.0Ϯ1.4 mm; PϽ0.001).…”
Section: Restenosismentioning
confidence: 98%
“…2,4,5) The percentage is quite consistent across different reports, although better results have been reported. 19,32) Worsening of blood pressure also occurs after the procedure. 4,5) Only if these formidable complications can be reasonably reduced will widespread adoption of PTRAS become more rational and persuading.…”
Section: Discussionmentioning
confidence: 99%